1993
DOI: 10.1210/mend.7.8.7901757
|View full text |Cite
|
Sign up to set email alerts
|

Substitutions of different regions of the third cytoplasmic loop of the thyrotropin (TSH) receptor have selective effects on constitutive, TSH-, and TSH receptor autoantibody-stimulated phosphoinositide and 3',5'-cyclic adenosine monophosphate signal generation.

Abstract: TSH and immunoglobulin G (IgG) preparations from patients with Graves' disease increase inositol phosphate as well as cAMP formation in Cos-7 cells transfected with rat TSH receptor (TSHR) cDNA. In a previous report, we mutated alanine 623 of the third cytoplasmic loop (residues 605-625) of the TSHR and showed it was critical for TSH and Graves' IgG initiation of phosphatidylinositol bisphosphate (PIP2) but not cAMP signaling. In this report, we substituted residues in the third loop of the TSHR with sequences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 0 publications
6
45
0
Order By: Relevance
“…3B). Thus, WT increased the basal CAMP level compared with the pSG5 control transfectant as previously described [2]. The maximal response compared with the basal levels of the same transfectant in the absence of TSH, was slightly but significantly decreased in B441 (Table 1).…”
Section: Functional Activities Of Mutant Receptorssupporting
confidence: 76%
See 3 more Smart Citations
“…3B). Thus, WT increased the basal CAMP level compared with the pSG5 control transfectant as previously described [2]. The maximal response compared with the basal levels of the same transfectant in the absence of TSH, was slightly but significantly decreased in B441 (Table 1).…”
Section: Functional Activities Of Mutant Receptorssupporting
confidence: 76%
“…Localization of sites in TSHR involved in each signal transduction is important for understanding the mechanism of receptor activation. We have investigated the 3rd [2,4] and 2nd [6] cytoplasmic loops of the TSHR by substituting the corresponding sequence from adrenergic receptors (ARs) and have found that: (i) the middle portion of the 2nd loop is important for agonistinduced CAMP production; (ii) widely distributed portions of the both loops are important for PIP* signaling; and (iii) both loops are important for regulating basal CAMP levels.…”
Section: Introduction 2 Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several examples where agonist-stimulated PLC activity of a G proteincoupled receptor is severely affected, when a single amino acid is mutated. The TSH receptor's capacity to generate IPs, for example, was markedly impaired when alanine at position 623 in the 3i loop was mutated to lysine or glutamic acid, but its capacity to activate adenylyl cyclase was unimpaired (48). It is puzzling, however, that the ␣1B-adrenergic receptor became constitutively activated with respect to stimulating PLC, when alanine at position 293, which is located at the same relative position as alanine 623 in the TSH receptor, was replaced with any amino acid (49).…”
Section: Discussionmentioning
confidence: 99%